2005
DOI: 10.2337/diabetes.54.9.2638
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Causes Remodeling of Cerebrovasculature via Differential Regulation of Matrix Metalloproteinases and Collagen Synthesis

Abstract: The risk of cerebrovascular disease is four-to sixfold higher in patients with diabetes. Vascular remodeling, characterized by extracellular matrix deposition and an increased media-to-lumen ratio, occurs in diabetes and contributes to the development of complications. However, diabetes-induced changes in the cerebrovascular structure remain unknown. Endothelin-1 (ET-1), a potent vasoconstrictor with profibrotic properties, is chronically elevated in diabetes. To determine diabetesmediated changes in the cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
141
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(147 citation statements)
references
References 46 publications
2
141
2
Order By: Relevance
“…Blood pressure was monitored either by telemetric method (as previously reported) (6) or via the tailcuff method (Kent Scientific, Torrington, CT), which we have previously validated on telemetry-implanted animals (5). After the spontaneous onset of diabetes, starting at 14 weeks of age, animals were divided into groups and treated for 4 weeks as follows: ET A receptor blockade, atrasentan (Abbott Labs) 5 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 in drinking water; ET B receptor blockade, A-192621 (Abbott Labs) 15 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 by oral gavage split into two daily doses; or vehicle as recommended by the manufacturer (6,16,17). Daily water consumption was measured for atrasentan treatment arm (6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood pressure was monitored either by telemetric method (as previously reported) (6) or via the tailcuff method (Kent Scientific, Torrington, CT), which we have previously validated on telemetry-implanted animals (5). After the spontaneous onset of diabetes, starting at 14 weeks of age, animals were divided into groups and treated for 4 weeks as follows: ET A receptor blockade, atrasentan (Abbott Labs) 5 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 in drinking water; ET B receptor blockade, A-192621 (Abbott Labs) 15 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 by oral gavage split into two daily doses; or vehicle as recommended by the manufacturer (6,16,17). Daily water consumption was measured for atrasentan treatment arm (6).…”
Section: Methodsmentioning
confidence: 99%
“…Fukuda et al (4) reported that blockade of ET-1 action inhibits aortic extracellular matrix (ECM) deposition. We showed that ET-1 levels are elevated and that an ET A antagonist prevents ECM deposition and MMP activation in middle cerebral arteries but not in the kidney of Goto-Kakizaki (GK) rats-a nonobese type 2 diabetes model (5,6). ET-1 mediates its diverse effects via distinct G protein-coupled receptor subtypes ETB AB and ETB BB .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, endothelin-1 was found to be responsible for the cerebrovascular diseases [32,33]. In previous studies, the application of endothelin-1 receptor antagonists created a cerebroprotective effect in diabetes-induced cerebrovascular dysfunction [34]. In our study, the reason why the endothelin-1 receptor antagonist was useful, particularly for the hippocampus and cerebellum, in diabetes-induced brain damage may have originated from the vasculoprotective effect.…”
Section: Discussionmentioning
confidence: 63%
“…Endothelin-1 and its signaling pathways are often upregulated during pathologic states. 7,[19][20][21][22] For these studies, we used our recently developed rat model of OSA. 6 We report three major findings from this study.…”
Section: Discussionmentioning
confidence: 99%